2009
DOI: 10.1080/14620316.2009.11512538
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrient absorption in chufa (Cyperus esculentusL. var.sativusBoeck.) in soilless culture

Abstract: Growth and nutrition in chufa 3The cultivated chufa is the botanical var. sativus of Cyperus esculentus L. The other four botanical vars., esculentus, leptostachyus, macrostachyus, and hermanii (Ter Borg and Schippers, 1992), also known as yellow nutsedge or tiger nut, can grow wild or as a weed, and are collectively called "weedy" (de Vries, 1991) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This refreshing and wholesome beverage has recently become popular in other countries, such as France, the UK, the USA and Argentina. Recent studies have reported increasing interest in nutsedge cultivation, mostly for food technology and biodiesel production in Brazil, Cameroon, China, Egypt, Hungary, the Republic of Korea, Poland, Turkey and the USA (Pascual-Seva et al 2009). Research on various aspects of nutsedge cultivation, like crop management techniques, cultivar selection and plant characterisation, is reviewed in Pascual et al (1999), and studies on nutsedge nutrition and fertilisation have also been conducted (Pascual-Seva et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This refreshing and wholesome beverage has recently become popular in other countries, such as France, the UK, the USA and Argentina. Recent studies have reported increasing interest in nutsedge cultivation, mostly for food technology and biodiesel production in Brazil, Cameroon, China, Egypt, Hungary, the Republic of Korea, Poland, Turkey and the USA (Pascual-Seva et al 2009). Research on various aspects of nutsedge cultivation, like crop management techniques, cultivar selection and plant characterisation, is reviewed in Pascual et al (1999), and studies on nutsedge nutrition and fertilisation have also been conducted (Pascual-Seva et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on its morphology, physiology, and control strategies when it is seen as a weed do exist, but little research has been performed regarding its cultivation. Nevertheless, two autochthonous clones and one clone of African origin were selected and characterized (Pascual et al, 2000); the accumulation of macronutrients was measured (583,109,355,295, and 58 kg ha -1 of N, P, K, Ca, and Mg, respectively; Pascual-Seva et al, 2009); diverse agronomic studies were made -including a study of the influence of the planting date on tuber yield (Pascual et al, 1999). This study showed that planting in mid-April rather than May extends the cultivation cycle and increases yield; however, planting in April is not always possible as previous crops are often awaiting harvest.…”
mentioning
confidence: 99%
“…In addition, with the previously obtained results of the dry weight (DW) of both the Echinochloa spp. and rice plants, the relative growth rate (RGR) was calculated, defined as the variation in the biomass per unit of time, for which two results from two dates are used [43,44]. The expression to be used for the calculation of the relative growth rate is the following, according to two times after sowing (DW 14 and DW 21 )…”
Section: Plant Measurementsmentioning
confidence: 99%